1990
DOI: 10.1017/s0004972700028161
|View full text |Cite
|
Sign up to set email alerts
|

On Lagrange interpolation with equidistant nodes

Abstract: A quantitative version of a classical result of S.N. Bernstein concerning the divergence of Lagrange interpolation polynomials based on equidistant nodes is presented. The proof is motivated by the results of numerical computations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 3 publications
0
16
0
Order By: Relevance
“…Approximation properties of the Lagrange interpolation polynomials to f l have attracted much attention in the 1990s and 2000s [7,8,13,[17][18][19][20][21]. In particular, Revers [17] proved that for N ¼ 2; 4; .…”
Section: Introductionmentioning
confidence: 99%
“…Approximation properties of the Lagrange interpolation polynomials to f l have attracted much attention in the 1990s and 2000s [7,8,13,[17][18][19][20][21]. In particular, Revers [17] proved that for N ¼ 2; 4; .…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been devoted to the approximation of x j j and x j j a by polynomials. For a survey of contributions to these topics, see Bernstein [2], Brutman and Passow [3], Byrne, Mills and Smith [4], Li and Saff [5], Revers [8], Runck [10] and Varga and Carpenter [11].…”
mentioning
confidence: 99%
“…Thus Lagrange interpolation on equidistant nodes diverges for a simple function such as h (x) . A quantitative version of Bernstein's result was developed by Byrne, Mills and Smith [3], who showed that if 0 < |x| < 1, then…”
Section: N) Nmentioning
confidence: 99%